PERSEPSI MAHASISWA TENTANG PENYELENGGARAAN PRAKTIKUM PADA PENDIDIKAN TINGGI TERBUKA JARAK JAUH (KASUS: PROGRAM STUDI AGRIBISNIS FMIPA UNIVERSITAS TERBUKA) - Sadjati, Ida Malati; Pertiwi, Pepi Rospina (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2013)
Agribusiness Study Program at Faculty of Mathematic and Natural Sciences, Univeritas Terbuka, has several practical courses. Practical work is mandatory and must be followed by every student. Formative evaluation of the implementation of practical work conducted in order to identify the characteristics of students participated in the practical work and to obtain some input and feedback from students about the quality of the implemetation of practical work that has ever done. This article describes the results of such of formative evaluation, especially in term of the students perceptions of the quality of practical manual, the quality of the practical work implementation in the field, as well as the obstacles faced. Eighty students from the entire 402 Agribusiness Study Program students who took the practical course at semester 2011.2 or 2012.1, from UPBJJ-UT Serang (Java) and UPBJJ-UT Pontianak (outside Java) were selected purposively. Only 53 out of 80 students who are willing to become informants of this evaluation .Evaluation results show that the characteristics of the students participating in practical work generally younger age, more women, residing far from UPBJJ-UT, has been working and educated at the high school. Most of students (over 80%) perceived the quality of practical guide as complete and clear in accordance with course competencies. This high quality of practical guide demonstrated by compliance of practical substances with the substance of learning materials (86.79%); completeness of practical guide component (84.90%), clarity of information in the practical guide (75.85%), and compliance of the substance of the practical guide with course substance, objectives and practical procedures (71.70%). Most of students too (81.76% ) perceived the implementation of practical work as very good and unhindered . The students felt that the implementation of practical work run well because it is supported by the meaningfulness of practical guide (86.79%), adequacy and affordability of practical work location (91.15%), ease of practical work procedures (92.45%), availability of equipment and practical materials ( 92.45%), ease of documentation of practical activities (94.34%), the availability and suitability of the educational background of the practical work instructors (94.34%), as well as good skills of the instructors in managing practical work (90.10%). While the lack of good quality of practical observation instruments and non standardized practical work financing is considered by students as factors that hinder the practical feasibility. Program Studi Agribisnis FMIPA-Universitas Terbuka memiliki beberapa mata kuliah berpraktikum. Praktikum bersifat wajib dan harus diikuti oleh setiap mahasiswa. Evaluasi formatif terhadap penyelenggaraan praktikum dilaksanakan dengan maksud mengidentifikasi karakteristik mahasiwa peserta praktikum dan mendapatkan masukan serta umpan balik dari mahasiswa tentang praktikum yang pernah dilakukannya. Artikel ini menjelaskan hasil evaluasi formatif terhadap penyelengaraan praktikum tersebut, terutama persepsi mahasiswa terhadap kualitas panduan praktikum, kualitas keterlaksanan praktikum di lapangan, serta hambatan yang dihadapi. Delapan puluh orang mahasiswa dari keseluruhan 402 orang mahasiswa PS Agribisnis yang menempuh praktikum pada semester 2011.2 atau 2012.1 di UPBJJ-UT Serang (Jawa) dan UPBJJ-UT Pontianak (Luar Jawa) dipilih secara purposive dan hanya 53 orang mahasiswa yang bersedia menjadi informan evaluasi ini. Hasil evaluasi menunjukkan bahwa karakteristik mahasiswa peserta praktikum umumnya berumur muda, lebih banyak perempuan, bertempat tinggal jauh dari UPBJJ-UT, sudah bekerja dan berpendidikan setingkat SMA. Kualitas panduan praktikum dipersepsikan lengkap, jelas, dan sesuai dengan kompetensi mata kuliah oleh sebagian besar mahasiswa (lebih dari 80%). Baiknya kualitas panduan praktikum tersebut ditunjukkan oleh keseuaian substansi materi praktikum dengan materi BMP (86,79%); kelengkapan komponen panduan praktikum (84,90%), kejelasan informasi dalam panduan praktikum (75,85%); dan kesesuaian substansi panduan praktikum dengan substansi MK, tujuan dan langkah-langkah praktikum (71,70%). Kualitas pelaksanaan praktikum dipersepsikan sangat baik dan tanpa hambatan oleh 81,76% mahasiswa. Keterlaksanaan praktikum berjalan dengan sangat baik karena ditunjang oleh kebermaknaan panduan praktikum (86,79%), kememadaian dan keterjangkauan tempat praktikum (91,15%), kemudahan langkah-langkah pelaksanaan praktikum (92,45%), ketersediaan alat dan bahan praktikum (92,45%), kemudahan pendokumentasian kegiatan praktikum (94,34%), ketersediaan dan kesesuaian latar belakang pendidikan instruktur (94,34%), serta baiknya keterampilan instruktur dalam mengelola praktikum (90,10%). Sementara kurang baiknya kualitas instrumen pengamatan praktikum dan tidak bakunya pembiayaan praktikum dianggap oleh mahasiswa sebagai faktor yang menghambat keterlaksanaan praktikum.